BUFFALO FECES GRANTING AND URINE OF SLUDGE PRODUCTION AND QUALITY OF GRASS ELEPHANT MINI ( PENNISETUM PURPUREUM SCHAMACH ) - Banjarnahor, Evi Reka; Hanafi, Nevy Diana; Tafsin, Ma'ruf; Sadeli, Achmad (Jurnal Peternakan Nusantara, 2017)
Community farms mostly only use the main products of the farm alone, did not see many more opportunities of byproducts such as feces and urine of livestock. Byproducts can be used for very useful organic fertilizers from crops especially forage for animal feed such as mini elephant grass (Pennisetum purpureum schamach) which is able to grow in various types of soil and is a grass of high nutritional value of fiber favored by livestock. The purpose of this study was to examine the effects from the provision of feces and urine buffalo mud and cutting intervals on the production and nutritional content of Pennisetum purpureum schamach. This research has been conducted at the Faculty of Agriculture, University of Sumatra Utara from July to October 2015. This study used Split Plot Design, consisting of cutting interval (4 weeks and 6 weeks) as main plot and type of fertilizer (control / no fertilizer application, mud buffalo feces, buffalo feces + non fermented urine buffalo and feces from buffalo mud + urine fermentation) as subplot. The observed variables were plant height, fresh production, dried production, number of tillers, crude protein and crude fiber from Pennisetum purpureum schamach forage. Cutting intervals have a significant effect on improving nutritional content such as crude protein and crude fiber of mini elephant grass. The interaction of the results showed that the provision of impurities from mud buffalo (feces and urine) gave a real effect to increase fresh production, dry matter production, plant height and number of mini elephant grass. The interaction of the results showed that the provision of impurities from mud buffalo (feces and urine) gave a real effect to increase fresh production, dry matter production, plant height and number of tillers mini elephant grass.. Provision of mud buffalo dung (feces and urine) showed a real interaction with fresh production, dry matter production, plant height, number of tillers, crude protein and crude fiber.Keywords:Pennisetum purpureum Schamach, feces, urine, and and forage productivity